Strategi Transformasi Digital dalam Tata Kelola Pemerintahan: Studi pada Kementerian Keuangan - Manik, Samuel Pardamean; Juwono, Vishnu (Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to analyze the Ministry of Finance's digital transformation implementation strategy and the factors that influence its success. This research method is qualitative with secondary data analysis consisting of report documents, working papers, scientific articles and other relevant documents. The findings from the research are three strategies implemented by the Ministry of Finance in Digital Transformation, namely preparing a Digital Transformation road map, building a data culture, and developing Enterprise Architecture. Factors that influence this success include a supportive and agile organizational culture, well-managed transformation activities, equalizing knowledge levels and capacity development, involvement of managers and employees, and development of digital strategies. Recommendations for further research are to analyze the effectiveness of digital transformation strategies using empirical studies and exploring the factors that influence the digital transformation of the public sector in Indonesia.